Comprehensive Assessment of Serum hsa_circ_0070354 as a Novel Diagnostic and Predictive Biomarker in Non-small Cell Lung Cancer - Huang, Yuejiao; Qin, Shiyi; Gu, Xinliang; Zheng, Ming; Zhang, Qi; Liu, Yupeng; Cheng, Chun; Huang, Kaibin; Peng, Chunlei; Ju, Shaoqing (Frontiers in Genetics, 2022)
Background: More and more studies have shown that circular RNAs (circRNAs) play an essential role in the occurrence and development of tumors. Hence, they can be used as biomarkers to assist in diagnosing tumors. This study focuses on exploring the role of circular RNA (hsa_circ_0070354) in the diagnosis and prognosis of non-small cell lung cancer (NSCLC). Materials and Methods: First of all, high-throughput sequencing was used to find the difference in the expression of circular RNA between NSCLC and adjacent tissues. The circRNAs with higher differences in expression were selected to verify their expressions in tissues, cells, and serum using qRT-PCR. Secondly, the hsa_circ_0070354 with a significant difference was chosen as the research goal, and the molecular properties were verified by agarose gel electrophoresis and Sanger sequencing, etc. Then, actinomycin D and repeated freeze-thaw were used to explore the stability and repeatability of hsa_circ_0070354. Finally, the expression of hsa_circ_0070354 in serum of 133 patients with NSCLC and 97 normal donors was detected, and its sensitivity, specificity, and prognosis as tumor markers were statistically analyzed. Results: Hsa_circ_007035 was highly expressed in tissues, cells, and serum of NSCLC, and it has the characteristics of sensitivity, stability, and repeatability. The ROC curve indicates that hsa_circ_007035 is superior to conventional tumor markers in detecting NSCLC, and the combined diagnosis is of more significance in the diagnosis. The high expression of hsa_circ_0070354 is closely related to the late-stage, poor differentiation of the tumor and the short survival time of the patients, which is an independent indicator of poor prognosis. Conclusions: Hsa_circ_007035 is not only a novel sensitive index for the diagnosis of NSCLC but also a crucial marker for bad biological behavior.